Evidence of aldosterone synthesis in human myocardium in acute myocarditis. (15th January 2019) - Cardona, Andrea; Baker, Peter; Kahwash, Rami; Smart, Suzanne; Phay, John E.; Basso, Cristina; Raman, Subha V.
Abstract: Background: Myocarditis may be self-limited but has been identified as an important contributor to downstream cardiomyopathy. Aldosterone mediates myocardial damage in various conditions, but has not been considered specifically as a therapeutic target for inflammatory damage in acute myocarditis. We sought to demonstrate local aldosterone synthesis in human myocardium affected by acute myocarditis. Methods: We evaluated myocardial samples obtained via endomyocardial biopsy (EMB) for expression of CYP11B2, the final and key enzyme for aldosterone synthesis, from patients with acute myocarditis and from stable heart transplant recipients with no evidence of rejection as negative controls. Excised adrenal glands from patients with aldosterone-secreting adenomas were used as positive controls. An experienced cardiovascular pathologist blinded to clinical information rated CYP11B2 stains as negative, positive, or borderline, also recording location of any CYP11B2-positivity. Results: Sixteen patients' EMB samples showing definite acute myocarditis were identified (50% female). CYP11B2 was positive in 13/16 cases (81%), typically showing diffuse intracardiomyocyte cytoplasmic staining, vs. 2/16 borderline stains in transplant controls (p < 0.001 myocarditis vs. negative controls). All 3 adrenalectomy samples stained positive for CYP11B2 (diffuse intracellular staining). Importantly, no myocarditis or transplant patients were on aldosterone antagonist therapy at the time of biopsy. Conclusions: In this proof-of-concept study, myocardium from patients with acute myocarditis demonstrates evidence and high prevalence of local aldosterone synthesis by immunohistochemistry that showed high accuracy, specificity, and sensitivity. Aldosterone warrants consideration as a specific target for therapy in patients with myocardial damage due to inflammation towards strategies that reduce downstream complications. Highlights: In-vivo, local production of aldosterone has never been demonstrated in subjects affected by biopsy-proven acute myocarditis. This work shows for the first time in humans local tissue synthesis of aldosterone in myocarditis not present in controls. These findings support further studies of aldosterone synthesis as a potential therapeutic target in acute myocarditis.